Storage yard layout at container terminals - Zouein, P. (2017)
Beirut Container Terminal (BCT) is the only port facility available in Lebanon that handles all sea trade Lebanon does with foreign countries. Optimizing its container handling and storage operations is vital for its growth and prosperity. This paper presents the re-layout of a portion of BCT storage yard that is operated by Beirut Container Terminal Consortium (BCTC). The re-layout is done using dedicated storage and is solved as an allocation problem where container types are re-allocated to Blocks in order to minimize the average distance traveled by internal trucks daily. Minimizing this distance is important in reducing the vessel turnaround time and offers BCTC the opportunity to reduce one of its major operating costs by reducing the number of internal trucks needed to service vessels daily. The proposed layout brought forth improvements in different performance measures of the storage system at BCT. It reduced the average distance traveled by internal trucks by 38.78% and increased the yard’s ground slots utilization and TEU throughput capacity by 8.25% and 4.73% respectively. The paper concludes by discussing the benefits of using dedicated storage over randomized or other storage methods for the re-layout of the storage yard at BCT.